Surrounding Rock Failure Characteristics and Water Inrush Mechanism of Roadway above the Aquifer in Nonuniform Stress Field. (29th January 2021) - Guo, Xiaofei; Li, Yongen; Li, Jun; Liu, Hongyu; Ma, Xianjie; Li, Ji; Li, Guoyu; Tan, Jihao
Abstract : The expansion of the roadway surrounding rock failure zone may connect the floor aquifer and cause the roadway water inrush. In order to reveal the mechanism of the roadway water inrush above confined water, we established the force model of the roadway surrounding rock above confined water in nonuniform stress field and studied the shape characteristics and expansion law of the roadway surrounding rock plastic zone. The results show that the roadway surrounding rock will form three kinds of plastic zone under different lateral pressure coefficients: circular, elliptical, and butterfly; when the shape of plastic zone is circular or elliptic, the maximum radius increases linearly with the increase of regional stress; when the shape is butterfly, the maximum radius increases exponentially with the increase of stress. Under the condition of a larger bidirectional stress ratio, the surrounding rock of the roadway will show butterfly-shaped failure, and small stress change will cause malignant expansion of the plastic zone; when the plastic zone is connected with the underlying aquifer, confined water of floor will enter the rock mass from the water diversion point and eventually flood into the roadway, causing floor water inrush.